Competitive adsorption characteristics of CH4/C2H6 gas mixtures on model substances, coal and shale. (1st November 2020) - Liu, Peng; Wang, Xiaofeng; Li, Xiaofu; Zhang, Ting; Du, Guichao; Liu, Wenhui
Abstract: Dynamic adsorption experiments were conducted on different samples to investigate the process and mechanism of competitive adsorption between CH4 and C2 H6 molecules. Based on adsorption breakthrough curves obtained from adsorption experiments, mathematical models of the adsorption process were established and related adsorption parameters were calculated. The results show that competitive adsorption between CH4 and C2 H6 molecules on adsorption materials can occur when adsorption materials have a significantly greater adsorption capacity of C2 H6 than that of CH4 . Meanwhile, fitted Yoon and Nelson model indicates different adsorption rate constants in CH4 and C2 H6 . Generally, samples with competitive adsorption characteristics, including 5 Å molecular sieve, 13X molecular sieve, activated carbon and shale, are characterized by obvious higher adsorption rate constant of CH4 than that of C2 H6 . Whereas, samples with no competitive adsorption characteristics, including 3 Å molecular sieve and coal, are characterized by almost same adsorption rate constants. The significantly greater adsorption capacity of C2 H6 than that of CH4 and obvious higher adsorption rate constant of CH4 than that of C2 H6 for samples in this study may result from a stronger induced force and dispersion force of C2 H6 with adsorbent compared with CH4 in existing of metal ion. During the increasing maturity stage of kerogen, competitive adsorption of methane and ethane can obviously influence the gas composition in free gas at relatively low maturity stage and such influence becomes weaker at higher maturity stage.